Treatment of condylomata acuminata caused by low-risk human papillomavirus with chloroquine phosphate gel - Li, Xiangling; Guan, Zhisheng; Liu, Qi; Yang, Wei; Huang, Jie; Yuan, Manli; Yu, Junlong (Frontiers in Medicine, 2023)
Objective To observe the stability and therapeutic effect of chloroquine phosphate gel on human condylomata acuminata (CA) caused by low-risk human papillomavirus (HPV). Methods The appearance, viscosity, pH, chloroquine concentration, deethylchloroquine concentration and content uniformity of chloroquine phosphate gel were examined for 24 months, the gel met the quality standards throughout the 24-month observation. A nude mouse model harboring CA xenografts was used to observe the therapeutic effect of this gel on CA in vivo. Results After 14 days of gel administration, compared with the control group, the treatment group had significantly smaller warts and significantly reduced DNA copy numbers of HPV6 and HPV11 in the wart tissues. Immunohistochemistry analysis of p53 protein expression in the wart tissues of the treatment group was significantly increased. Conclusion Chloroquine phosphate gel was stable and effective against CA, possibly through the promotion of p53 protein expression to induce apoptosis, leading to the involution of warts.